Determinants of manager pay in German state-owned enterprises and international public policy implications: 3-year study for sectors, performance and gender - Ulf Papenfuß; Christian Schmidt (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2015)
Empirical studies have shown that state-owned enterprises (SOEs), and especially the compensation of topmanagers, are very relevant to the performance and sustainable provision of public services. Whereas there are numerous studies on the compensation of top-management of private sector organizations, almost no empirical studies have been conducted for SOEs. This paper examines the determinants and disclosure of top-management compensation from 176 SOEs in eleven sectors over three financial years by assessing 498 annual statements. As a methodological contribution, the paper demonstrates the relevance for adjusting raw data from financial statements to obtain meaningful performance figures in order to represent the real economic situation. This provides perspectives for research on organizational success for several disciplines. In contrast to the transparency requirements 75.2% of the companies do not disclose information about compensation in their annual financial statements. For the 233 annual financial statements with disclosed pay, firm size has a significant influence on the level of compensation. The number of employees, an important indicator for the relevance of the public service, has lower influence than balance sheet total and turnover. Furthermore, managers earn more in profitable sectors than in loss-making sectors; however loss-making sectors often have a special relevance of for society and for the sustainable provision of public services. With regard to laws which also formulate financial goals for SOEs, there appears to be no link between financial performance ratios and the level of compensation. However, a strong and highly significant correlation exists between the developments of return on equity (ROE) and performance-based components. Return on total assets (ROA), which seems to be a better figure in this context to link performance and pay, was found to have no association. Regarding the discussion about a bonus-malus-system the data show far more compensation rises than decreases. Women employed in top-management positions were found to earn, on average, notably less than men. This finding has special implications for the prevailing public policy discussion about the gender pay gap in which SOEs have a special responsibility. In the ongoing debate about the appropriateness of compensation, the findings indicate that the level of compensation is not particularly strongly determined by the indicators that were investigated in this study. The paper provides new empirical insights, research perspectives and concrete international implications for public policy making as well as for practitioners.
Keywords: G3; G38; L32; M4; 330; State-Owned Enterprises; Top-Manager Compensation; Public Corporate Governance